Rearrangement of CRLF2 in B-progenitor– and Down syndrome–associated acute lymphoblastic leukemia - Mullighan, Charles G; Collins-Underwood, J Racquel; Phillips, Letha A A; Loudin, Michael G; Liu, Wei; Zhang, Jinghui; Ma, Jing; Coustan-Smith, Elaine; Harvey, Richard C; Willman, Cheryl L; Mikhail, Fady M; Meyer, Julia; et al. (Nature genetics, 2009)
Charles Mullighan and colleagues report a recurrent rearrangement of CRLF2 in B-progenitor and Down syndrome-associated acute lymphoblastic leukemia. Their genetic and functional evidence indicates that CRLF2 cooperates with activated JAK2 to promote leukemogenesis. Aneuploidy and translocations are hallmarks of B-progenitor acute lymphoblastic leukemia (ALL), but many individuals with this cancer lack recurring chromosomal alterations. Here we report a recurring interstitial deletion of the pseudoautosomal region 1 of chromosomes X and Y in B-progenitor ALL that juxtaposes the first, noncoding exon of P2RY8 with the coding region of CRLF2 . We identified the P2RY8-CRLF2 fusion in 7% of individuals with B-progenitor ALL and 53% of individuals with ALL associated with Down syndrome. CRLF2 alteration was associated with activating JAK mutations, and expression of human P2RY8-CRLF2 together with mutated mouse Jak2 resulted in constitutive Jak-Stat activation and cytokine-independent growth of Ba/F3 cells overexpressing interleukin-7 receptor alpha. Our findings indicate that these two genetic lesions together contribute to leukemogenesis in B-progenitor ALL.